Contributions to some Corydiinae genera (Blattodea: Corydioidea: Corydiidae) from China. Issue 21 (11th June 2018) - Qiu, Lu; Che, Yan-Li; Wang, Zong-Qing
ABSTRACT: New findings on Chinese Corydiinae are presented and new taxa are described and illustrated: Ctenoblatta impubis gen. and sp. nov., Minicorydia maoxiana gen. and sp. nov. and Ergaula nepalensis (Saussure) is newly recorded from China. The occurrence of two species of Polyphaga Brullé, P. plancyi Bolívar and P. obscura Chopard, in China are confirmed. A key to Chinese Corydiinae genera is provided as well as checklists for extant Polyphaga and Ergaula . http://zoobank.org/urn:lsid:zoobank.org:pub:F428E561-2A57-4DAD-8855-5879AB4599FB